Three-channel dependent mid/side coding framwork for multichannel 3D audio - Shi DONG; Rui-min HU; Yu-hong YANG; Xiao-chen WANG; Wei-ping TU (Tongxin xuebao)
The conventional mid/side coding method is discussed and generalized to a three-channel dependent M/S cod-ing (3D-M/S) method. Moreover, a codec framework based on 3D-M/S is proposed which enables the 3D-M/S to work for three-dimensional audio systems with more than three channels. It is experimentally shown that proposed framework gets about 25% objective quality improvement compared with independent coding, and only increases about 1/3 com-plexity of the PCA method.